Konstruksi Feminisme Perempuan Sumba - Stara Asrita (ARISTO, 2019)
In much feminist literatures show that women often have been underneath men power. This study aims to analyze about women representation in film “Marlina si Pembunuh dalam Empat Babak”. The method is critical discourse to see hidden contexts in this film with a gender perspective. Some scenes show that woman had a choice to protect herself. The main character of this film, Marlina tried to give a poison and murdered the thieves who want to robber and rape her. Those Marlina’s acts were different if we comparing with women stereotype that existed. Women were described as a second person, gentle and depend on men. The feminist movement in this film show women’s emancipation in social life, struggle to protect her body and family problems in Sumba’s woman.